Outbreak Column 22: How to manage an outbreak - Curran, Evonne T (J Infect Prev, 2017)
This outbreak column uses the Health Protection Scotland (HPS) Outbreak Process and Algorithm to examine and reflect on a published outbreak report. The report involved an extensively drug-resistant Acinetobacter baumannii in an oncology unit. High-reliability theory is then used to reflect on how the outbreak was managed and consider how best to improve local outbreak prevention, preparedness, detection and management. The conclusion of this exercise is that if the possibility of an era of untreatable infections caused by antibiotic-resistant organisms is to be significantly postponed, Infection Prevention and Control Teams must improve their ability to get others to prevent cross-transmission in the absence of recognised risks.